Low-cost test setup for motorcycle protective clothing abrasion examination - Dietrich Spädt; Imane Moulefera; Al Mamun; Marah Trabelsi; Lilia Sabantina (Communications in Development and Assembling of Textile Products, 2021)
The personal protective equipment and protective clothing for motorcyclists reduce physical injuries to victims of road accidents. Therefore, it is important that the protective clothing complies with a number of test standards, which must be taken into account during the manufacturing process. However, the EN17092-1 to 6 standard does not necessarily correspond to a real accident situations and these testing procedures are time consuming. In this study, a simple and inexpensive self-constructed device for testing the abrasion resistance of motorcycle protective clothing was developed and evaluated. Different types of textiles and leather with and without coating were tested and compared. According to the results of this study, not only leather but also textiles offer good abrasion resistance results. The results show that the strength of an impact significantly changes the abrasion resistance. The developed test method can provide a good alternative as a low-cost and simple test method of abrasion resistance of motorcycle protective clothing.